High Mobility, High Carrier Density SnSe2 Field‐Effect Transistors with Ultralow Subthreshold Swing and Gate‐Controlled Photoconductance Switching - Yuan Huang; Eli Sutter; Bruce A. Parkinson; Peter Sutter (Advanced Electronic Materials)
Abstract 2D and layered semiconductors are considered as promising electronic materials, particularly for applications that require high carrier mobility and efficient field‐effect switching combined with mechanical flexibility. To date, however, the highest mobility has been realized primarily at low carrier concentration. Here, it is shown that few‐layer/multilayer SnSe2 gated by a solution top gate combines very high room‐temperature electron mobility (up to 800 cm2 V−1s−1), along with large on‐off current ratios (>105) and a subthreshold swing below the thermodynamic limit (50 mV per decade) in field‐effect devices, at exceptionally large sheet carrier concentrations of ≈1013 cm−2. Observed mobility enhancements upon partial depletion of the channel point to near‐surface defects or impurities as the mobility‐limiting scattering centers. Under illumination, the resulting gap states give rise to gate‐controlled switching between positive and negative photoconductance. The results qualify SnSe2 as a promising layered semiconductor for flexible and wearable electronics, as well as for the realization of advanced approaches to photodetection.